Chemical reactivity between sol–gel deposited Pb(Zr, Ti)O3 layers and their GaAs substrates. Issue 39 (2nd September 2016) - Meunier, B.; Largeau, L.; Regreny, P.; Penuelas, J.; Bachelet, R.; Vilquin, B.; Wague, B.; Saint-Girons, G.
Abstract : We show how chemical interactions between the growing material and the substrate affect the crystallization of Pb(Zr, Ti)O3 (PZT) thin films on SrTiO3 -templated GaAs substrates. Abstract : We show how chemical interactions between the growing material and the substrate affect the crystallization of Pb(Zr, Ti)O3 (PZT) thin films on SrTiO3 -templated GaAs substrates. A liquid PZT precursor (sol) is spin-coated on STO/GaAs pseudo-substrates grown by molecular beam epitaxy and crystallized by annealing under air. Complete crystallization of the PZT layers cannot be achieved due to significant oxidation of the GaAs substrate which enhances As diffusion through the structure and further formation of parasitic compounds containing Pb, Sr and As due to the strong chemical affinity between As anions and Pb and Sr cations. These mechanisms are extensively studied based on X-ray diffraction measurements carried out in situ during annealing and on transmission electron microscopy experiments including energy-dispersive X-ray analyses.